PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH, BUDAYA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN BUMIAYU - Ani Latpiatun Apidah; Noor Miyono; Titik Haryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problems in this research are (1) is there a positive influence of the principal's managerial skills on the performance of public elementary school teachers in Bumiayu District?, (2) is there a positive influence of school culture on the performance of public elementary school teachers in Bumiayu District?, (3) is there a positive influence of school culture on the performance of public elementary school teachers in Bumiayu District? positive influence of work motivation on the performance of public elementary school teachers in Bumiayu District?, and (4) is there a positive influence of the principal's managerial skills, school culture and work motivation together on the performance of public elementary school teachers in Bumiayu District?. The aims of this research are (1) to determine the magnitude of the influence of school principals' managerial skills on the performance of public elementary school teachers in Bumiayu District, (2) to determine the magnitude of the influence of school culture on the performance of public elementary school teachers in Bumiayu District, (3) to determine the magnitude of the influence work motivation on the performance of state elementary school teachers in Bumiayu District, (4) to determine the magnitude of the influence of the principal's managerial skills, school culture and work motivation together on the performance of state elementary school teachers in Bumiayu District. The population in this study were all state elementary school teachers in the Bumiayu subdistrict, Brebes Regency, totaling 502 people. A sample of 222 people was obtained using simple random sampling. The data collection method used is the questionnaire method. The data analysis used is descriptive analysis, prerequisite testing and hypothesis testing which includes simple linear regression analysis to determine the influence of the principal's managerial skills on teacher performance and multiple regression analysis to determine the influence of the principal's managerial skills, school culture and work motivation together. on teacher performance. To analyze the data using the SPSS 23 program facilities. The results of the prerequisite tests from the research data showed that the data was normally distributed, homogeneous, linear, not multicollinear and there was no heteroscedasticity. From the hypothesis test, it was found that there was a positive influence of the principal's managerial skills on teacher performance with a contribution of 0.629 or 62.9%. There is a positive influence of school culture on teacher performance with a contribution of 0.626 or 62.6%. There is a positive influence of work motivation on teacher performance with a contribution of 0.514 or 51.4%. There is a positive influence of the principal's managerial skills, school culture and work motivation together on teacher performance with a contribution of 0.695 or 69.5%.